PELAKSANAAN KONSTRUKSI BASEMENT PADA PROYEK GEDUNG KANTOR MANDIRI AREA SOLO PT ADHI KARYA - , HERJUNA WIDHI ARYA DWIUTAMA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Basement construction is an economical and efficient solution to overcome the limitations of area/land needed to build or to construct a building, especially the high rise building. In the implementation, basement construction as an underground structure must calculate and pay attention to technical aspects, the environmental aspects are also an important aspect on the basement construction. The selection of the retaining wall construction specifications are the most important aspect to build the basement. The Mandiri (Solo) Office Building Project is using the Contiguous Pile construction as the retaining wall. Those Contiguous Piles are constructed using the mixed concrete with K-175 specification and with 800 mm on the size of the diameter. From the result of the basement construction calculation obtained that the turap is 24,2 m on the length and with 85 cm on thickness which is safe to be used on this basement construction, and for the pile capacity support (Qall) is 32,7 Ton and 2.128 kN. Meanwhile, the flowrate of the pump (Qp) is 5,93 lt/s with 1,5 â 2 pk on the power. And to hold the force caused by the pressure of water to come up, the dimension design of the work floor is 1 m.